Folate deficiency in patients seeking treatment of alcohol use disorder. (1st November 2017) - Sanvisens, Arantza; Zuluaga, Paola; Pineda, Miriam; Fuster, Daniel; Bolao, Ferran; Juncà, Jordi; Tor, Jordi; Muga, Robert
Highlights: Almost one in four patients with AUD demonstrates low serum folate levels. Macrocytosis is associated with folate deficiency in contemporary patients seeking treatment of AUD. Neither age nor gender are associated with folate deficiency in AUD patients. Abstract: Introduction: Nutritional deficiency is frequent in patients with an alcohol use disorder (AUD). We aimed to analyze serum and erythrocyte folate deficiency in a case series of patients that initiated treatment of AUD. Patients and methods: A cross-sectional study in patients admitted for detoxification between 2007 and 2015 was performed. Sociodemographic characteristics, history of alcohol consumption, type of alcohol, and medical co-morbidity were assessed at admission. Blood samples for biochemistry and hematological parameters were collected at admission. Logistic regression models were used to establish predictors of folate deficiency. Results: 211 patients (79.1% men) were eligible; age at admission was 46 years [IQR:40-51], and the amount of alcohol consumption was of 160 g/day [IQR:120-200]. Thirty four percent of patients had macrocytosis (MCV > 100 fL), 12.8% had anemia, 23% of cases presented with serum folate deficiency and 7% presented with erythrocyte folate deficiency. Most (69%) of the patients with serum folate deficiency had normal erythrocyte folate levels. In univariate analysis, macrocytosis (OR = 3.4, 95%CI:1.7-6.6), alcohol-related liver disease (ARLD) (OR = 2.5, 95%CI:1.0-6.1) and drinking alcoholic beverages other than beer (OR = 3.3, 95%CI:1.5-7.3) were associated with folate deficiency. However, only macrocytosis was significantly associated with serum folate deficiency in multivariate analysis (OR = 3.1, 95%CI:1.1-8.9). Macrocytosis ( P <  0.001), ARLD ( P  = 0.01) and the type of alcohol consumption ( P <  0.001) were factors associated with erythrocyte folate deficiency in univariate analysis. In multivariate analysis only macrocytosis remained significantly associated to erythrocyte folate deficiency ( P  = 0.037). Conclusion: Folate deficiency is a relatively frequent finding in contemporary, middle-aged patients with AUD, and macrocytosis is significantly associated with the deficiency.